Penegakan Hukum Pidana Terhadap Penyebaran Berita Bohong Di Sosial Media - dwinanda, Renza Ardhita (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2019)
The rapid development of Information Technology affects people’s behavior and lifestyle. The cheaper the Information Technology-based devices and internet access have an impact on the increasing number of internet users. Most internet users access the internet, especially accessing social media, on the other hand HOAX, the expression of hatred, develops rapidly through social media. HOAX effect, the utterance of hatred is very large in the social life of the community. Online Social Media became a means of spreading HOAX, so many people were affected by HOAX, so that the Anti Hoax Task Force was formed by the government. But to overcome HOAX the government is not strong enough to work alone, the community and various parties must participate in helping against HOAX. hoaxes (deception) are regulated in Law Number 11 Year 2008 concerning Information and Electronic Transactions. Article 28 paragraph (1) and (2) Spreading false news can be a criminal offense if it is not- Nothing in Law Number 11 Year 2008 concerningInformation and Electronic Transactions Article 28 paragraphs (1) and (2) are fulfilled.The responsibility for lending false news is a number11 of 2008 concerning Information and Electronic Transactions in conjunction with Law Number 19 of 2016 concerning Amendments to Law Number11 of 2008 concerning Information and Electronic Transactions Article 45A paragraph (1)and (2). Only accepting someone is limited to sharing information but has no intention to approve, create, add or subtract Such information, can be discussed as a court action